CRISPR/Cas9-Mediated Knockout of the Dicer and Ago2 Genes in BHK-21 Cell Promoted Seneca Virus A Replication and Enhanced Autophagy - Wu, Xiaoyan; Wang, Shuo; Li, Chen; Shi, Jianli; Peng, Zhe; Liu, Chang; Han, Hong; Ma, Yingru; Zheng, Limei; Xu, Shaojian; Du, Wei; Li, Jun; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
RNA interference (RNAi) is a major form of antiviral defense in host cells, and Ago2 and Dicer are the major proteins of RNAi. The Senecavirus A (SVA) is a reemerging virus, resulting in vesicular lesions in sows and a sharp decline in neonatal piglet production. In this study, CRISPR/Cas9 technology was used to knock out Ago2 and Dicer genes in BHK-21 cell line used for SVA vaccine production. Cell clones with homozygous frame-shift mutations of Ago2 and Dicer genes were successfully identified. The two knockout cell lines were named BHK-DicerΔ- and BHK-Ago2Δ-. Results showed that the two genes knockout cell lines were capable of stable passage and the cell growth rate did not change significantly. The replication rate and virus titers of SVA were significantly increased in knockout cell lines, indicating that RNAi could inhibited SVA replication and the knockout cell lines has a promising future in the production of SVA vaccine. In addition, compared to normal cells, autophagy was enhanced after SVA infectiong in knockout cell lines, indicating for the first time that RNAi inhibited autophagy.